Selective and Sensitive ZnO Quantum Dots Based Fluorescent Biosensor for Detection of Cysteine - Kamaci, Umran Duru; Kamaci, Musa (SPRINGER/PLENUM PUBLISHERS, 2021)
In the present article, a novel and effective ZnO quantum dots-based fluorescent probe has been developed for the detection of cysteine in different solutions. Firstly, melamine-based fluorescent pre-probe was successfully synthesized via condensation reaction and, then ZnO quantum dots (QDs) were homogenously dispersed into this solution. This fluorescent probe was used for the detection of cysteine in different solutions such as bovine serum albumin and tap water. ZnO QDs were characterized using XRD, nano-particle size analyzer, and FE-SEM techniques. The size of the ZnO QDs was calculated as 28.03 +/- 9.86 nm, and 31.95 +/- 10.02 nm from Scherrer's equation and nano-particle size analyzer, respectively. The developed fluorescent probe was exhibited a highly selective and sensitive response to the detection of cysteine. Also, the proposed fluorescent probe has a larger Stokes shift value (236 nm). The limit of detection and linear range of ZnO QDs-based fluorescent biosensor were found as 0.642 mu M and 0.1-600 mu M, respectively.
Keywords: ZnO quantum dots; Biosensor; Cysteine; BSA; Melamine; FLUOROMETRIC-DETERMINATION; CARBON DOTS; POLY(AZOMETHINE-URETHANE); NANOPARTICLES; SENSOR; PROBE; FE3+; Biochemistry & Molecular Biology; Chemistry